As apropriações da obra de Pierre Bourdieu no campo educacional brasileiro - Afrânio Catani; Denice Catani; Gilson Pereira (Universidade do Minho, 2002)
From a research conducted with 20 journals specialized in education, published between 1971 and 2000, the present text analyses the appropriation forms from Pierre Bourdieus work in the Brazilian educational field. 355 articles published in those periodics making references to the sociologist constitute the basic corpus for the analysis of the peculiarities of the brazilian interpretation of the author.